Menyoal Legal Standing Permohonan Penundaan Kewajiban Pembayaran Utang oleh Pemegang Polis Asuransi - Gultom, Xander Gorga; Agustina, Rosa (Al-Adalah: Jurnal Hukum dan Politik Islam, 2023)
In Indonesia, the postponement of debt payment obligations (PKPU) is a certain period of time granted by law through a commercial court decision. It gives both parties opportunity to deliberate on ways of paying their debts by providing a payment plan for all or part of the debt, including to restructure the debt. The purposes of this study is to find out the arrangement of pospotnment of debt payment obligations in Indonesia and the legal standing of a policy holder in applying suspension of debt payment obligations. This study is a normative research type and use Statute Approach, Conseptual Approach, and Case Approach. In collecting the data, examining the regulation of insurance company bankruptcy according to positive law and the legal standing of insurance customers as creditors to carry out company’s bankruptcy is done by the researcher. The results show that the regulations that apply both in law and insurance Law Number 40 of 2014, OJK Law, Law Number 37 of 2004 concerning Bankruptcy and Delays Debt Payment Obligations, and regulations related to the topic of scrutiny can be applied properly. Based on this study, it is expected that rules that have been set can be expressly and clearly used as a basis in submitting applications and handling cases of PKPU. It is also hoped that the Panel of Judges can consider the legal position of the party submitting for the applications.